2020
DOI: 10.22146/jh.57647
|View full text |Cite
|
Sign up to set email alerts
|

Semiotic Landscapes: Scaling Indonesian Multilingualism

Abstract: This article presents a very preliminary description of a sample of photos of signage (e.g. posters, signs, billboards) drawn from around six hundred photos taken in Bandung in January 2019. Drawing upon scholarship on value and scale in general, and work on semiotic landscapes in particular, this paper seeks to extend earlier analysis of multilingual signage in Indonesia. I explore how an analysis of this signage can provide insights into multilingualism, inequality, and mobility in Indonesia, as well as how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Moreover, the issues of inequality and economic mobility were brought by Goebel (2020) when researching signs in the main streets in Bandung and some of the nearby neighborhoods. In his attempt to portray the signs of Chineseness, he found little signage containing Chinese characters out of the six hundred or so pictures taken in the central district of Bandung.…”
Section: Focal Issues Associated With Ll Studiesmentioning
confidence: 99%
“…Moreover, the issues of inequality and economic mobility were brought by Goebel (2020) when researching signs in the main streets in Bandung and some of the nearby neighborhoods. In his attempt to portray the signs of Chineseness, he found little signage containing Chinese characters out of the six hundred or so pictures taken in the central district of Bandung.…”
Section: Focal Issues Associated With Ll Studiesmentioning
confidence: 99%
“…Arabic also exists to represent the Islamic identity of the schools. A different perspective, the semiotic landscape, is adopted by Goebel (2020) in revealing Bandung's cityscape. It was found that signage presents multilingualism, inequality, human mobility, and social, political, and economic effects on the city's multilingualism.…”
Section: Linguistic Landscape Studies In Indonesiamentioning
confidence: 99%
“…The contestation happens in the public space due to the imbalance position of languages in the social life of a speech community in which there must be a dominant and marginal language as the result of language policy, commercial consideration, and the close relationship of a certain language to a speech community (Lotherington, 2013). Further development of LL theory arises, and it is defined as an interdisciplinary branch of the sociolinguistics of globalization which concerns the languages on outdoor signs in public areas and its correlation with semiotics, sociology, politics, geography, and economy (Barni & Bagna, 2015;Goebel, 2020). Ben-Rafael et al (2006) differentiate outdoor signs into two major groups: top-down and bottom-up.…”
Section: Linguistic Landscapementioning
confidence: 99%
“…LL yang sering juga disebut dengan semiotik lanskap adalah salah satu bingkai cara pandang fenomena linguistik di suatu daerah yang merupakan bagian dari sosiolinguistik globalisasi, linguistik antropologi, dan linguistik etnografi (Goebel, 2020). Hal tersebut menyebabkan kajian LL bersifat interdisipliner yang melibatkan aspek semiotik, sosiologi, politik, geografi, dan ekonomi (Barni & Bagna, 2015).…”
Section: Kerangka Teoriunclassified